1994
DOI: 10.1021/j100099a041
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Wave Damping in Heterogeneous Monolayers

Abstract: We studied capillary wave damping in heterogeneous monolayers of triglyceride at the air-water interface over a range of surface wavelengths (70-300 pm) using a light scattering technique. In addition, we studied the monolayer morphology using a Brewster angle microscope. We found that the morphology has a strong effect on the capillary wave damping. In the gaslliquid expanded (GLE) coexistence region the monolayer forms a two-dimensional foam structure, where "bubbles" of gas phase are separated by regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…Systematic study of capillary waves on thin film surfaces began in the late 60s of the previous century and since then a great number of relevant publications exists [38][39][40][41][42][43]. Artificial wave propagation in foams was studied specifically by Sun et al [44], bending mode in free films by Bergmann [45] and wetting films by Schulze et al [23,35].…”
Section: Acoustically Exited Surface Wavesmentioning
confidence: 99%
“…Systematic study of capillary waves on thin film surfaces began in the late 60s of the previous century and since then a great number of relevant publications exists [38][39][40][41][42][43]. Artificial wave propagation in foams was studied specifically by Sun et al [44], bending mode in free films by Bergmann [45] and wetting films by Schulze et al [23,35].…”
Section: Acoustically Exited Surface Wavesmentioning
confidence: 99%
“…3. However, bearing in mind the high accuracy of the measurements of the wavelength which can be achieved with the use of modern experimental methods, [8][9][10][11][12] it is easy to reveal a noticeable influence of the multiple scattering.…”
Section: ͑34͒mentioning
confidence: 99%
“…8 On the other hand, recent studies have shown high sensitivity of the capillary wave characteristics to the surface rheological properties and made possible the use of the cap-illary wave method in the investigation of heterogeneous insoluble monolayers. [8][9][10][11][12][13][14] According to some authors, 8,11 one of the obstacles to this is the absence of an adequate theory of surface wave propagation in systems with tangentially heterogeneous interface. However, this is not quite correct: The first theoretical study of the surface wave scattering by two-dimensional viscoelastic particles appeared several years ago.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments on capillary wave propagation at fluid-gas interfaces covered with surfactants can show a dramatic increase in the damping rate of the surface capillary waves. [10][11][12][13][14][15] In these experiments, a wave maker generates a capillary wave and either the dispersion relation, wave amplitude, or the width of the spectral peaks generated from light scattering of a thermally fluctuating interface, is measured, and the damping coefficient characterizing the attenuation of the interface deformation is extracted. The damping coefficient is observed to depend on the surface coverage and appears to have a maximum near the regime where surface phases coexist.…”
Section: Introductionmentioning
confidence: 99%